2021
DOI: 10.1111/jmg.12606
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic PTtd evolution of the Mesoproterozoic Pur‐Banera supracrustal belt, Aravalli Craton, northwestern India: Insights from phase equilibria modelling and zircon–monazite geochronology of metapelites

Abstract: The Pur-Banera belt of metasedimentary rocks, in the Bhilwara region of the Aravalli Craton, northwestern India, constitutes a Mesoproterozoic rift-related supracrustal sequence. The Pur-Banera belt, while containing psammitic, calcareous, and ferruginous metasediments, is dominated by garnet-staurolite-kyanite-bearing metapelites. Here we integrate data on outcrop-and microscopic-scale deformation structures with pseudosection modelling and zircon-monazite geochronology to decipher the P-T-t-d evolution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 94 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Conventional thermobarometry is a widely applied technique to constrain the P–T conditions of an equilibrium mineral assemblage using exchange and net transfer reactions. However, many studies have shown that the conventional thermobarometry results obtained for the prograde and peak metamorphic episodes are usually underestimated due to elemental diffusion during the prolonged high‐grade peak metamorphism (Caddick et al, 2010; La Roche et al, 2015) and retrograde cooling process (D'Souza et al, 2021; Spear & Florence, 1992), respectively. Therefore, textural relationships should be carefully considered while pairing different minerals for estimating equilibrium P–T conditions of different metamorphic episodes.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional thermobarometry is a widely applied technique to constrain the P–T conditions of an equilibrium mineral assemblage using exchange and net transfer reactions. However, many studies have shown that the conventional thermobarometry results obtained for the prograde and peak metamorphic episodes are usually underestimated due to elemental diffusion during the prolonged high‐grade peak metamorphism (Caddick et al, 2010; La Roche et al, 2015) and retrograde cooling process (D'Souza et al, 2021; Spear & Florence, 1992), respectively. Therefore, textural relationships should be carefully considered while pairing different minerals for estimating equilibrium P–T conditions of different metamorphic episodes.…”
Section: Resultsmentioning
confidence: 99%
“…These authors also reported that the age range between 1,725–1,621 Ma represents granulite metamorphism and exhumation and related them to the Delhi basin opening. D'Souza et al (2019); D'Souza, Prabhakar, Sheth, and Xu (2021) have studied the depositional time of the Pur‐Banera supracrustals (basin within the Mangalwar Complex) using U–Pb zircon and U–Th–Pb monazite technique on paragneisses and structural data and found to vary between 1.6 and 1.3 Ga. Their model of Pur‐Banera rift basin evolution also supports this assertion that the sedimentation processes took place during 1.6–1.3 Ga which is synchronous with the Delhi basin (1.7–1.0 Ga), whilst 1.3 Ga of the Pur‐Banera marks the closure event (compressional event) and deformation. So, the G3 type amphibolites could be associated with the depositional age of the sediments of the Pur‐Banera basin (pull‐apart basin), that is, 1.6–1.3 Ga, and were emplaced largely around 1.6 Ga during the rifting stage.…”
Section: Regional Geological Settingmentioning
confidence: 99%
“…Additionally, due to deformations that occurred millions of years ago in the Aravalli-Delhi mountain ranges, the Sandmata rocks that are found along the terrane boundary have been bent (Naha & Halyburton, 1974; Sen, 1980; Srivastava, 2001; Bhowmik et al 2010; Singh et al 2010, 2020; Roy et al 2012, 2016; Tiwari & Biswal, 2019; Biswal et al 2022; Tiwari et al 2022). Therefore, the older ages of the Mangalwar and Sandmata complexes are reset to younger ages, particularly in the northern part of the Banas shear zone (Bhowmik & Dasgupta, 2012; Ahmad & Mondal, 2016; Kumar et al 2019; D’Souza et al 2021). It is generally agreed that the collision between the Bundelkhand craton and the Marwar craton was the primary driving force behind the orogeny that resulted in the development of the ADMB (Bhowmik et al 2010; Singh et al 2010, 2020; Tiwari & Biswal, 2019; Biswal et al 2022; Tiwari et al 2022).…”
Section: Introductionmentioning
confidence: 99%